تأثير التشعيع على الخصائص البصرية لأغشية CdS المحضرة بطريقة التبخير الحراري في الفراغ - عليوي, هند فاضل (Al-Nahrain Journal of Science, 2018)
Effect of Gamma Radiation with different doses )0,1,5,10) Mrad was studied on the optical properties for CdS films of 1μm thickness prepared by thermal evaporation at pressure (10-6torr) on glass substrate. The optical properties of CdS films, absorbance, transmittance and reflectance have been studies in the wavelength range of (300-900)nm. The refractive index, extinction coefficient, absorption coefficient and dielectric constant were also studied as afunctionof photon energy and optical energy gap of allowed direct and forbidden transition. Radiation is change films colour to dark yellow and increase the value of absorption coefficient, extinction coefficient and dielectric onstant while occurs decreasing on the Reflectance, Refractive index and dielectric constant .